2003
DOI: 10.1007/s00497-003-0175-7
|View full text |Cite
|
Sign up to set email alerts
|

Pollen tube growth and early ovule development following self- and cross-pollination in Eucalyptus nitens

Abstract: Controlled self-and cross-pollinations were conducted on flowers of five mature Eucalyptus nitens trees. Levels of self-sterility of the trees ranged from 25.8 to 93.6%. Pollen tube numbers in styles and ovule penetration by pollen tubes was investigated 2 weeks after pollination by fluorescence microscopy. There were no significant differences between treatments in the number of pollen tubes present in styles or in the percentage of ovules penetrated by pollen tubes. Embryology of material harvested 2 and 4 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
23
0
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 30 publications
(33 reference statements)
1
23
0
2
Order By: Relevance
“…There is little research on the breeding system of E. nitens, but Moncur et al (1995) estimated a 75% outcrossing rate in this species, and Pound et al (2003) found that levels of self-incompatibility in E. nitens ranged from 25.8 to 93.6%. Self-pollination is definitely possible in E. nitens (Griffin et al 1987;Tibbits 1988), particularly in areas where the presence of natural pollinators is low, and pollen load is poor.…”
Section: Flowering Levelmentioning
confidence: 99%
See 1 more Smart Citation
“…There is little research on the breeding system of E. nitens, but Moncur et al (1995) estimated a 75% outcrossing rate in this species, and Pound et al (2003) found that levels of self-incompatibility in E. nitens ranged from 25.8 to 93.6%. Self-pollination is definitely possible in E. nitens (Griffin et al 1987;Tibbits 1988), particularly in areas where the presence of natural pollinators is low, and pollen load is poor.…”
Section: Flowering Levelmentioning
confidence: 99%
“…The reticent or shy flowering of E. nitens has hindered the breeding programme and the production of improved seed, for plantation establishment. Globally, the species is known as a light and infrequent flowerer and produces small seed crops (Pound et al 2003). In South Africa, the species often only becomes reproductively mature at 10 to 15 years of age if grown in a plantation situation (Eldridge et al 1993; and requires winter chilling, or hormonal treatments to replace the chilling, if flowering is to occur earlier (Gardner and Bertling 2005).…”
Section: Introductionmentioning
confidence: 99%
“…It is thought that outcrossing is high in E. nitens due to successful late-acting selfincompatibility mechanisms in the species (Hodge and White 1993;Pound et al 2003).…”
Section: Coefficient Of Relationship and Outcrossing Ratementioning
confidence: 99%
“…Moncur et al (1995) estimated that outcrossing was at a level of 75% in an E. nitens seed orchard, and Pound et al (2003) found that levels of self-incompatibility in E. nitens ranged from 25.8 to 93.6%. The species demonstrates preferential outcrossing and appears to have a late-acting selfincompatibility system operating to reduce the production of selfed seed (Pound et al 2003;Tibbits 1989).…”
mentioning
confidence: 99%
See 1 more Smart Citation